KARAKTERISTIK SOSIAL EKONOMI ANAK JALANAN KOTA SAMARINDA - Rahcmad Budi Suharto (Faculty of Economics and Business Mulawarman University, 2016)
The purpose of this research is to find out about the social economic characteristics of child hobo in Samarinda City. Using qualitative methods, sampling use accidental sampling. Obtained data from observation, interview, and documentation will be recorded in field notes which usually contains two aspects which is descriptive and reflective records. Findings from this child hobo characteristics researchs shows that most of them on age 6 to 18 years old consists of 50% boys and 50% girls. These childs Hobo, 80,5% dropped out and 19,4% stays on school. Most of these kids origins is from Celebes 66,7%, and few of them came from Borneo 25%. Even fewer came from Nusa Tenggara Timur and Java. The majority of these child hobo still had their family intact, so that 80,6% of them still lives with their respective parents. Based on jobs, 75% worked as street performers, 19,44% as newspaper seller and 5,56% as asongan seller . This jobs is one of the most promising because they need less to none talent and finesse. Most of them 52,78% works 6 to 10 hours a day with earnings about 20 to 50 thousands rupiah a day 50%.Keyword: Child Hobo, School, Jobs and Social Economic